Restitution : seeing past loss and abandonment - Greenway, Paul Wayne (Rhodes University, Faculty of Humanities, Department of Fine Art, 2013)
This dissertation is concerned with loss and abandonment, and together with the practical component, titled Restitution, forms part of a Master of Fine Art degree submission. Both loss and abandonment can take many forms, from the straightforward deterioration, departure or removal of objects to the more complex deterioration of memory, responsibility and dignity. It seems though, that the question, "What has been lost?" is one that is always asked once it is too late. The loss becomes irretrievable and one is left only with fragments and traces. In Chapter 1 issues of liminality and the precariousness of being between states is addressed. Dignity of the 'other', in this case the deceased pauper, is interrogated especially with reference to complicity, forensic investigation and the forensic aesthetic. Chapter 2 outlines photographic representation, with attention given to posthumous portraiture, the punctum and memory in the service of permanence and authenticity. Chapter 3 considers the ambition and purpose of the artist through a critique centred on contemporary photographic artist, Sally Mann. Throughout the thesis and exhibition, I am concerned with loss as it relates physically to objects. Metaphorically, I investigate loss and abandonment in relation to dignity and responsibility. In so doing I view death as being the ultimate form of loss, as there is physical loss of the body, as one part of the whole that makes up 'the person', as well as the psychological and emotional loss that attends the passing of life. The delayed burial of the deceased therefore is seen to be evidence of abandonment at its extreme. I end by positioning my conclusion around a stop animation series in which I dug a grave and buried a pauper at Mayfield cemetery.
Keywords: Digitally printed materials; Bereavement in art